1980
DOI: 10.1113/jphysiol.1980.sp013432
|View full text |Cite
|
Sign up to set email alerts
|

Sodium channel permeation in squid axons. I: Reversal potential experiments.

Abstract: SUMMARY1. Na channel reversal potentials were studied in perfused voltage clamped squid giant axons. The concentration dependence of ion selectivity was determined with both external and internal changes in Na and ammonium concentrations.2. A tenfold change in the internal ammonium activity results in a 42 mV shift in the reversal potential, rather than the 56 mV shift expected from the Goldman, Hodgkin, Katz equation for a constant PNa/P~N 14 ratio. However, changing [Na]0 tenfold at constant internal [NH4] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
118
1

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 42 publications
6
118
1
Order By: Relevance
“…VOLUME 85 -1985 site from the internal membrane surface. This estimate assumes the Na channel to be a one-ion pore (Hille, 1975) under these experimental conditions (however, see Begenisich and Cahalan, 1980). The average fractional electrical distance determined in this manner was 0.10 ± 0.02 (three axons) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…VOLUME 85 -1985 site from the internal membrane surface. This estimate assumes the Na channel to be a one-ion pore (Hille, 1975) under these experimental conditions (however, see Begenisich and Cahalan, 1980). The average fractional electrical distance determined in this manner was 0.10 ± 0.02 (three axons) .…”
Section: Resultsmentioning
confidence: 99%
“…Possible interactions between blocking cations and the Na conductance pathway have serious practical implications for the use of ionic substitutes that may otherwise be presumed to be inert (see, e.g., Begenisich and Cahalan, 1980). In particular, experimental substitution of internal K by certain cations is frequently used to eliminate contributions of ion movement through K channels from ionic current records under voltage clamp.…”
Section: Introductionmentioning
confidence: 99%
“…Parts C and D of Fig. 14 (Hille, 1975;Begenisich & Cahalan, 1980). Energies, G, of the barriers and wells are given in dimensionless units, multiplied by R, the gas constant, and T, the absolute temperature.…”
Section: A Molecular Interpretation Of the Kinetic Effects Of Tnbsmentioning
confidence: 99%
“…Previous work (Chandler & Meves, 1965;Cahalan & Begenisich, 1976) and the first paper in this series (Begenisich & Cahalan, 1980) have shown that the selectivity of Na channels appears to depend on the concentration of many different permeant ions applied at the axoplasmic membrane surface. Concentration-dependent selectivity is but one of several permeation properties that cannot be accounted for within the Nernst-Planck and Goldman-Hodgkin-Katz formulations of electrodiffusion in membranes.…”
Section: Introductionmentioning
confidence: 99%